Composite scintillators for a wide range of problems in detection of ionizing radiation - Karavaeva, N.L. (Functional Materials, 2014)
We have developed a new type of scintillation materials composite scintillators. It has been shown that such materials can be obtained both on the basis of organic (fast neutron detection) and inorganic (thermal neutron detection) grains. The use of radiation-resistant materials and wide range of scintillation materials for preparation of grains allows using such approach not only for radioecology (weak fluxes), but also in high energy physics. The promising results on radiation stability of composite scintillators are preliminary, and further studies are necessary.